2022
DOI: 10.3389/fevo.2022.797350
|View full text |Cite
|
Sign up to set email alerts
|

An Individual-Based Model of the Red Alga Agarophyton chilense Unravels the Complex Demography of Its Intertidal Stands

Abstract: Algal demographic models have been developed mainly to study their life cycle evolution or optimize their commercial exploitation. Most commonly, structured-aggregated population models simulate the main life cycle stages considering their fertility, growth and survival. Their coarse resolution results in weak predictive abilities since neglected details may still impact the whole. In our case, we need a model of Agarophyton chilense natural intertidal populations that unravels the complex demography of isomor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 72 publications
0
19
0
Order By: Relevance
“…In the red macroalgae Chondrus crispus (reviewed in Collén et al, 2014) and C. verrucosus (Bellgrove & Aoki, 2008), many intertidal populations are gametophyte biased. In contrast, ploidy dominance varies among species but sporophytes are often observed at greater frequencies in many populations in the Gracilariales (reviewed in Kain & Destombe, 1995, but also see Vieira et al, 2022), the Ceramiales (Cecere et al, 2000), some species of the Gigartinales (e.g., Hypnea musciformis ; Caires et al, 2013), as well as in other red macroalgae, such as Pterocladiella capillacea (Patarra et al, 2020) and green macroalgae, such as two Ulva spp. (Du et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the red macroalgae Chondrus crispus (reviewed in Collén et al, 2014) and C. verrucosus (Bellgrove & Aoki, 2008), many intertidal populations are gametophyte biased. In contrast, ploidy dominance varies among species but sporophytes are often observed at greater frequencies in many populations in the Gracilariales (reviewed in Kain & Destombe, 1995, but also see Vieira et al, 2022), the Ceramiales (Cecere et al, 2000), some species of the Gigartinales (e.g., Hypnea musciformis ; Caires et al, 2013), as well as in other red macroalgae, such as Pterocladiella capillacea (Patarra et al, 2020) and green macroalgae, such as two Ulva spp. (Du et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Kamiya and Kawai (2002) showed evidence that maternal care provides germlings with additional nutrients leading to increased growth rates as compared to carpospores released from cystocarps which had been excised from the female gametophyte shortly after fertilization. Based on the extensive investigation of each life cycle stage in G. chilensis , Vieira et al (2022) observed that varying environmental factors throughout the year favored different stages. Whether similar mechanisms maintain both life cycle stages in Antarctic Plocamium sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations